UBI JALAR UNGU MEMPERBAIKI KADAR SUPEROXIDE DISMUTASE DAN JUMLAH FOAM CELL TIKUS YANG DIPAPAR ASAP ROKOK - Ariestiningsih, Ayuningtyas Dian; Nihlawati, Anita; Handayani, Feti Noor (Lembaga Penerbitan Unversitas Esa Unggul, 2018)
Cigarette smoke is a source of free radicals contains carcinogenic chemical substances.The purple sweet potatoes contains anthocyanins which has potential antioxidant activities to neutralize free radicals. This research aim was to know the effect of purple sweet potatoes extract on the levels of lung’s superoxide dismutase (SOD) and number of foam cells in aorta of wistar rat which were exposed to cigarette smoke. This research was an experimental study with complete random design and post test only control group design. The twenty five wistar divided into five groups: control group (P0); group was only exposed to cigarette smoke (P1); groups were exposed to cigarette smoke and purple sweet potatoes extract in dose of 0,065 (P2), 0,13 (P3), and 0,26 (P4) g/day for 90 days. Data was analyzed by One Way Anova and Post Hoc Tukey HSD test. The result of this study indicate that the levels of lung’s SOD were 25,26 ± 2,35; 13,11 ± 3,85; 19,24 ± 3,95; 9,20 ± 6,23; 24,53 ± 5,75 unit/mg, while the average number of foam cells in aorta were 19,68 ± 7,74; 40,40 ± 10,67; 27,16 ± 4,28; 25,92 ± 5,24; 16,80 ± 4,22 for P1, P2, P3, P4, and P5 respectively. There was different SOD levels in lung and foam cells in aorta significantly between control and treatment groups (p < 0,05). It was concluded that the purple sweet potatoes extract can increase SOD levels in lung and decrease foam cell in aorta of wistar rat which were exposed to cigarette smoke. Keywords: purple sweet potatoes, SOD, foam cell, cigarette smoke